STRATEGI PARTAI AMANAT NASIONAL (PAN) DALAM MENINGKATKAN PEROLEHAN SUARA PADA PEMILIHAN UMUM LEGISLATIF KOTA PEKANBARU TAHUN 2019 - ", Fauza; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
One of the political parties in Indonesia that participates in the contestation in every political event, namely Partai Amanat Nasional. Partai Amanat Nasional in the legislative general election in Pekanbaru City in 2019 there was an increase of 57.58 percent or as many as 22,466 votes compared to the vote in 2014 which obtained 30,503 votes, where in 2019 the National Mandate Party was able to collect 52,969 votes.            The purpose of this research is to find out the Partai Amanat Nasional strategy in increasing vote acquisition in the Pekanbaru City legislative general election in 2019. This study uses descriptive qualitative techniques. In collecting data, the author uses interview and documentation techniques.            The results of this study indicate that the Partai Amanat Nasional strategy in increasing vote acquisition in the 2019 Pekanbaru City legislative general election, it was based on the use of the strategy proposed by Petter Schroder, namely offensive and defensive strategies. Partai Amanat Nasional used strategy offensive proven by each electoral district can get one seat. In theelectoral district IV, the one who gets one seat is the new member who registers with the Partai Amanat Nasional this shows that new members become the Partai Amanat Nasional strategy in increasing vote acquisition in the legislative general election in Pekanbaru City in 2019. It is proven that legislative candidates campaign in various ways, one of which is using mass media and the Partai Amanat Nasional does not discriminate in accepting members but remains selective in accordance with the applicable AD/ART rules. Keywords: Strategy, Offensive, Defensive, Legislative Election.